Comedia y melancolía en la narrativa neopoliciaca : (Vázquez Montalbán, Taibo II, Padura) - Tongeren, Carlos van (Foro hispánico, 2019)
In recent years, both the intellectual lucidity of melancholy and the liberating potentials of comedy, irony and humour have emerged as central preoccupations in critical theory and literary criticism. In this book, Carlos van Tongeren offers a thorough and innovative reflection on the intersections between comedy and melancholy. Through detailed readings of almost twenty novels by three key writers of detective fiction in the Spanish-speaking world, he puts diverse melancholic attitudes towards the past and the multiple "surplus" values of comedy into a clear historical perspective. As such, this book provides a profound understanding of how comedy and melancholy have shaped Hispanic detective fiction following wider political and cultural developments in the post-totalitarian contexts of Spain, Mexico and Cuba. En años recientes, la lucidez intelectual de la melancolía y los potenciales liberadores de la comedia, la risa y el humor han emergido como preocupaciones centrales en la teoría crítica y crítica literaria. En este libro, Carlos van Tongeren ofrece una reflexión profunda e innovadora sobre las intersecciones entre la comedia y la melancolía. A través de una lectura detallada de una veintena de novelas de representantes clave de la ficción policiaca en el mundo hispanohablante, el autor muestra cómo la comedia y la melancolía han influido en la ficción policiaca en español, de acuerdo con cambios políticos y culturales más amplios en los contextos postotalitarios de España, México y Cuba.